2011
DOI: 10.1099/vir.0.034801-0
|View full text |Cite
|
Sign up to set email alerts
|

The effects of NS5A inhibitors on NS5A phosphorylation, polyprotein processing and localization

Abstract: Hepatitis C virus (HCV) non-structural protein 5A (NS5A) is a multi-functional protein that is expressed in basally phosphorylated (p56) and in hyperphosphorylated (p58) forms. NS5A phosphorylation has been implicated in regulating multiple aspects of HCV replication. We recently reported the identification of a class of compounds that potently inhibit HCV RNA replication by targeting NS5A. Although the precise mechanism of inhibition of these compounds is not well understood, one activity that has been descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 37 publications
3
45
0
Order By: Relevance
“…2C), suggesting that the mechanism of antiviral action of NS5A inhibitors do not involve the rupture of NS5A-NS5A interactions. While our studies were in progress, a report showed that NS5A inhibitors such as BMS-790052 impair hyperphosphorylation of NS5A and that this activity is mediated by sequences within Domain 1 (38).…”
Section: Ns5a Forms Dimers Directly Through Domain I Interactions-mentioning
confidence: 88%
“…2C), suggesting that the mechanism of antiviral action of NS5A inhibitors do not involve the rupture of NS5A-NS5A interactions. While our studies were in progress, a report showed that NS5A inhibitors such as BMS-790052 impair hyperphosphorylation of NS5A and that this activity is mediated by sequences within Domain 1 (38).…”
Section: Ns5a Forms Dimers Directly Through Domain I Interactions-mentioning
confidence: 88%
“…HCV nonstructural proteins were expressed from replicon plasmids in BHK-21 cells by using a modified vaccinia virus-T7 (MVA-T7) expression system or following transfection of replicon RNA into Huh7.5 cells as previously described (26,33). Western blot analysis of NS5A and NS3 proteins was performed as previously described (26).…”
Section: Methodsmentioning
confidence: 99%
“…12 In this context, it is noteworthy that preformed replication complexes (RCs) are refractory to inhibition of HCV RNA replication by NS5A inhibitors. [12][13][14] Furthermore, NS5A inhibitors have been shown to induce redistribution of NS5A from endoplasmic reticulum-derived foci, [12][13][14] possibly to lipid droplets, 12 and limit hyperphosphorylation of NS5A, [14][15][16] although these effects may be indirect. Finally, it has been suggested that NS5A inhibitors may disrupt interactions of NS5A with HCV RNA, other viral proteins, and/or host factors that are coopted by NS5A during the HCV life cycle.…”
Section: Hcv Ns5a Inhibitors Disrupt Replication Factory Formation: Amentioning
confidence: 99%